RESPONDENTS OPINION TOWARDS THE SERVICES AVAILED FROM PUBLIC DISTRIBUTION SYSTEM, TANGEDCO AND E-SEVA CENTRES IN COIMBATORE DISTRICT - M, Sumathy. (The journal of contemporary issues in business and government, 2021)
Today e-governance has become an integrated part of democracy countries. Also, the importance of computerization and e-governance in introducing transparency and accountability in the functioning of governments is obvious. There are many stumbling blocks like poverty, illiteracy, poor IT infrastructure, lack of awareness, and political as well as psychological problems in the growth of e-governance in India. Legal system is still very archaic for the growth of e-governance. Low emphasis on process re-engineering, poor management of knowledge and human resources, lack of coherent government policies, government unwilling to commit funding, corruption, inefficiency, and incompetence present in public services and welfare/ development projects, lack of co-ordination between different service agencies are also recognized as major challenges for implementing an effective e- governance. Unless all these issues and problems are dealt with e-governance can't really take-off in India. The present study is immensely useful to general public and Government. The study will assist general public to understand the type of E Services offered by the Government of Tamilnadu and to understand the level of utilization of E Services and problems faced by them on using E Services, thereby Government could take suitable steps to contain the problems faced by general public and to assist general public to avail necessary services from Government without corruption. Further, the study also offer suitable suggestions to Government for successful implementation of E Governance practices in Coimbatore and to offer quick services to the public at their door step and to make Coimbatore as Corruption free.